The innovative- technological development of Finland as the formation factor of “knowledge economy” - Pobirchenko, V.; Sharova, O. (Культура народов Причерноморья, 2014)
In this article discusses innovative - technological development as the formation factor of
“knowledge economy”, on the example of Finland. Identifying of innovation development preconditions in
Finland. The main purpose of the study is: identification of assumptions and factors of innovative and
technological development of Finland. To achieve this goal in this article, consistently solved the following
problems: 1) an assessment of the factors of innovation and technological development of the country in modern
conditions, 2) Studied the characteristics of factors territorial distribution of innovation and technological
development, 3) defined territorial differences of innovation and technological development of the regions in
Finland and trends of their evolution. This article presents the characteristics of the Finnish national innovation
systems, and also characterized the development features of modern Finnish national innovation system.
Presenting the indicators that describes the competitive stability of Finnish regional clusters, describing
typology in terms of innovative - technological development of the regions. And finally forming of conclusions
about innovative - technological activities of the regions in Finland. У даній статті розглядається інноваційно – технологічний розвиток регіонів, як фактор
формування «економіки знань», на прикладі Фінляндії. Виявляються передумови інноваційно –
технологічного розвитку територій Фінляндії. Особливу увагу приділено так званим факторам «нової
економіки», а також утворенню інноваційно – технологічних кластерів. Описується типологія регіонів
за рівнем інноваційно – технологічного розвитку. В данной статье рассматривается инновационно – технологическое развитие регионов,
как фактора формирования «экономики знаний», на примере Финляндии. Выявляются предпосылки
инновационно – технологического развития территорий Финляндии. Особое внимание уделено так
называемым факторам «новой экономики», а также образованию инновационно – технологических
кластеров. Описывается типология регионов по уровню инновационно – технологического развития.